10.24843 The Analysis of Indonesian Transitive and Intransitive Verbs Found in the Translation of Possum Magic - An Australian Classic by BIPA Students of La Denpasar - Utami, I Made Verayanti; Apriliani, Kadek; Sugiarti, Dian Pramita (e-Journal of Linguistics; Vol 12 No 2 (2018): eJL-July, 2018)
Languages in the world have its own system, specifically in verbs classification. Indonesian has two classifications in verbs, transitive and intransitive verbs. It is similar to English that there are transitive and intransitive verbs. Therefore the translation of transitive and intransitive from English into Indonesian can be done. Thus, this research is designed to analyze the Indonesian transitive and intransitive found in the translation of an Australian classic entitled Possum Magic done by BIPA (Indonesian for Non-Native Speaker) students, the translation technique used by the students in translating the transitive and intransitive verbs in the narrative text, and the problems faced by the students in translating the transitive and intransitive verbs. The data focused on the translation of Possum Magic- An Australian Classic from English to Indonesian done by ten students of BIPA at La Denpasar BIPA School. The method of collecting the data in this research was direct observation method. There were two techniques used in collecting the data. The first is reading the English version of Possum Magic - An Australian Classic and the translation done by BIPA students. The second technique is choosing the sentences that represent the use of transitive and intransitive verbs in Indonesian. After the data collected, they were analyzed. The techniques of analyzing the data followed three steps. First, the categorization of the verbs classification was done. Then, the translation techniques used by BIPA students in translating the transitive and intransitive verbs in the narrative text were identified. Last, the problems faced by the students in translating the transitive and intransitive verbs were analyzed. The result of the research was shown that there were variations of the English transitive and intransitive verbs translation into Indonesian done by the students, those are the English transitive (ET) translated into Indonesian transitive (IT) verbs, English transitive (ET) translated into Indonesian intransitive (II), and English intransitive (EI) translated into Indonesian intransitive (II). There were two techniques used by the students to translate the transitive and intransitive verbs from English to Indonesian, they are literal technique and adaptation technique. Most of the translations were acceptable in Indonesian, but still there are some problems faced by the students in the process of translating the transitive and intransitive verbs. The problems found in this research were categorized as linguistic untranslatability that proposed by Catford (1965).